Preparation of Highly Stable and Effective N-Doped TiO2@SiO2 Aerogel Catalyst for Degradation of Organic Pollutants by Visible Light Catalysis. (3rd November 2019) - Tang, Shiyun; Ran, Jingyu; Guo, Junjiang; Tang, Anjiang
Abstract : To obtain high stable and effective TiO2 photocatalyst, nano-N-doped TiO2 @SiO2 (TiO2−x Nx @SiO2, 0 ≤ x ≤ 2) composite aerogels were synthesized by the sol-gel method combined with supercritical drying and direct oxidation process. The adsorption/photocatalytic degradation efficiency of TiO2−x Nx @SiO2 aerogels was evaluated by the degradation of RhB in aqueous solution under visible light irradiation. The physiochemical properties of the aerogels were examined by XRD, FT-IR, TEM, SEM, TG/DTA, and BET methods. It was found that the specific surface areas of all TiO2−x Nx @SiO2 samples exceeded 700 m 2 /g and exhibited a honeycomb porous structure with fine particulate morphology. Photocatalytic activity tests show that the 500-TiO2 @SiO2 composite aerogel exhibits the best adsorption/photocatalytic degradation rate for RhB, which obtained about 80% of the degradation rate in 30 min under visible light and over 95% after 120 min. On the one hand, the SiO2 aerogels can significantly inhibit the phase transition of TiO2, and the nano TiO2 can be highly dispersed in the SiO2 aerogels; On the other hand, if the oxidation temperature is selected properly, the N-doped TiO2−x Nx @SiO2 aerogel can be obtained by simple TiN@SiO2 aerogel oxidation.